2012
DOI: 10.1145/2287718.2287725
|View full text |Cite
|
Sign up to set email alerts
|

Graded computation tree logic

Abstract: Abstract. In modal logics, graded (worlds) modalities have been deeply investigated as a useful framework for generalizing standard existential and universal modalities, in such a way they can express statements about a given number of immediately accessible worlds. These modalities have been recently investigated with respect to the propositional µ-calculus, which provide formulas exponentially more succinct, without affecting the computational complexity for the extended logic, i.e., the satisfiability probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…It also introduces a graded extension of SL, called GSL. However, in contrast with our work and [4] (and by extending an idea of counting paths in [5,10]), GSL provides a quite intricate way of counting strategies: it gives a semantic definition of equivalence of strategies, and the graded modalities count non-equivalent strategies. While this approach is sound, it heavily complicates the model-checking problem.…”
Section: Introductionmentioning
confidence: 88%
“…It also introduces a graded extension of SL, called GSL. However, in contrast with our work and [4] (and by extending an idea of counting paths in [5,10]), GSL provides a quite intricate way of counting strategies: it gives a semantic definition of equivalence of strategies, and the graded modalities count non-equivalent strategies. While this approach is sound, it heavily complicates the model-checking problem.…”
Section: Introductionmentioning
confidence: 88%
“…Graded modalities are the equivalent to qualified number restrictions in Description Logics. EXPTIME bounds for the Computational Tree Logic extended with graded modalities are proven by [13]. In [9], it is shown that the fully enriched μ-calculus is undecidable.…”
Section: A Related Workmentioning
confidence: 97%
“…Other expressive logics with counting (arithmetic) constraints have been recently studied [10], [11], [9], [12], [13], [14], [15]. In [10], basic modal logic extended with Presburger constraints is shown to be in PSPACE.…”
Section: A Related Workmentioning
confidence: 99%
“…The formal definition of semi-alternating pushdown tree automata follows. 6 A semi-alternating pushdown tree automaton is a tuple A = Σ, D, Γ, Q , q 0 , , δ, F where Σ is a finite input alphabet, D is a finite set of directions, Γ is a finite pushdown store alphabet, Q is a finite set of states, q 0 ∈ Q is the initial state, / ∈ Γ is the pushdown store bottom symbol, and F is an acceptance condition, to be defined later. δ is a finite transition function δ : (d, q, β), where d is a direction, q is a state, and β is a string of pushdown store symbols.…”
Section: Semi-alternating Pushdown Tree Automatamentioning
confidence: 99%
“…The only subtle point involves handling the binary-encoded graded modalities without increasing the complexity with respect to the propositional μ-calculus. For more details see[5,6].…”
mentioning
confidence: 99%